STRATEGI PENINGKATAN LITERASI SISWA DI SD QTA AN NAWA MELALUI PROGRAM LITERASI DAN HOLISTIK INTEGRATIF - Alfiyah, Dinda Nurul; Izzah, Armiya Nur Lailatul; Chusna, Cahya Amalia (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Literacy is an essential foundation in primary education, particularly for first-grade students who are still in the early stages of developing reading, writing, and text comprehension skills. However, literacy achievement in Indonesia continues to face various challenges, including low reading interest, limited availability of age-appropriate reading materials, and insufficient nutrition, which affects children’s concentration and memory. This study focuses on strategies to improve students’ literacy through an integrative holistic literacy approach at SD QTA An Nawa, which combines reading activities with nutritional interventions in the “Saturday Literacy and Nutrition” program. The research employed a qualitative approach with a case study design. The subjects of the study included the principal, first-grade homeroom teacher, and first-grade students. Data were collected through in-depth interviews, participatory observation, and documentation study. The findings reveal that bringing favorite storybooks from home and healthy meals not only improved reading skills but also fostered learning motivation and nutrition awareness among students. The success of the program was supported by teachers’ involvement, parents’ participation, and students’ enthusiasm, although some challenges remained, such as limited parental understanding of nutrition and inconsistent discipline in following the program. In conclusion, the holistic integrative literacy strategy proved effective in enhancing literacy skills while fostering healthy habits, making it a potentially innovative model for adoption in other primary schools. ABSTRAK Literasi merupakan pondasi esensial dalam pendidikan dasar, terutama bagi siswa kelas 1 yang masih berada pada tahap awal mengembangkan kemampuan membaca, menulis, dan memahami teks. Meski demikian, capaian literasi di Indonesia masih menghadapi berbagai hambatan, mulai dari rendahnya minat baca, terbatasnya ketersediaan bacaan yang sesuai usia, hingga kurangnya asupan gizi yang berpengaruh terhadap konsentrasi dan daya ingat anak. Penelitian ini berfokus pada strategi peningkatan literasi siswa melalui pendekatan literasi holistik integratif di SD QTA An Nawa, yang menggabungkan kegiatan membaca dengan intervensi gizi dalam program “Sabtu Literasi dan Gizi.” Metode penelitian menggunakan pendekatan kualitatif dengan desain studi kasus. Subjek penelitian terdiri atas kepala sekolah, guru wali kelas 1, dan siswa kelas 1. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, serta studi dokumentasi. Temuan penelitian menunjukkan bahwa kegiatan membawa buku cerita pilihan dari rumah dan bekal sehat tidak hanya meningkatkan keterampilan membaca, tetapi juga menumbuhkan motivasi belajar serta kesadaran gizi pada siswa. Keberhasilan program didukung oleh keterlibatan guru, partisipasi orang tua, dan antusiasme siswa, meskipun masih terdapat hambatan berupa keterbatasan pemahaman gizi di kalangan orang tua dan kurangnya kedisiplinan sebagian peserta. Kesimpulannya, strategi literasi holistik integratif terbukti efektif meningkatkan kemampuan literasi sekaligus membentuk kebiasaan hidup sehat, sehingga berpotensi menjadi model inovatif yang dapat diadaptasi oleh sekolah dasar lainnya.